2020
DOI: 10.1007/s12020-020-02432-z
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after pituitary surgery in adult Cushing’s disease: a systematic review on diagnosis and treatment

Abstract: Purpose Recurrence after pituitary surgery in Cushing’s disease (CD) is a common problem ranging from 5% (minimum) to 50% (maximum) after initially successful surgery, respectively. In this review, we give an overview of the current literature regarding prevalence, diagnosis, and therapeutic options of recurrent CD. Methods We systematically screened the literature regarding recurrent and persistent Cushing’s disease using the MESH term Cushing’s disease and recurrence. Of 717 results in PubMed, all manuscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 141 publications
2
30
2
2
Order By: Relevance
“…Rates for persistence of CD or recurrence after initial remission were reported with a great variability depending on the ratio of micro-/macroadenoma, the experience of the surgeons and the definition for persistence and recurrence (1,2). Based on meta-analyses the rates for persistence and recurrence after initial TSS ranged from 22 to 24% (persistence) (3,4,5) and 10-12% (recurrence) (4), respectively. Studies with a longer follow-up showed higher recurrence rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates for persistence of CD or recurrence after initial remission were reported with a great variability depending on the ratio of micro-/macroadenoma, the experience of the surgeons and the definition for persistence and recurrence (1,2). Based on meta-analyses the rates for persistence and recurrence after initial TSS ranged from 22 to 24% (persistence) (3,4,5) and 10-12% (recurrence) (4), respectively. Studies with a longer follow-up showed higher recurrence rates.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with a longer follow-up showed higher recurrence rates. Although the highest risk for recurrent disease is observed in the first five years (6), it can occur as late as several decades after surgery and lifelong surveillance for recurrence is essential. Second-line treatments in persistent and recurrent CD include repeat transsphenoidal surgery, fractionated pituitary radiation and radiosurgery, medical therapy targeting ACTH and cortisol excess, and bilateral adrenalectomy (BADX).…”
Section: Introductionmentioning
confidence: 99%
“…Regular follow-ups after first successful surgery are recommended [5,13,14] but a unifying consensus on specific clinical and biochemical testing and follow-up intervals has not been established so far. Also, recurrence criteria are not universally agreed on [15].…”
Section: Discussionmentioning
confidence: 99%
“…Our remission criteria for RCD and PCD were as follows: (I) The 24 UFC level was reduced to eucortisolism levels (20-100 µg/24 hour), including hypocortisolism levels (<20 µg/24 hour) and undetectable 24 UFC (10). (II) Serum cortisol levels decreased to within or below the normal range (5.0-25.0 µg/dL) and values lower than 5 or 3 µg/dL were specified (10,11). Data were obtained after withdrawal of glucocorticoids.…”
Section: Remission Criteriamentioning
confidence: 99%